Breaking the siege of hypoxia and lactate: carrier-free flexible dual-enzyme protein vesicle to ignite photodynamic-immune storm in head and neck squamous cell carcinoma - Yan Zhou; Xiaoquan Xu; Ziyue Zu; Shangyu Lu; Wei Lu; Xi Luo; Nan Zhong; Yang Liu; Zhaogang Teng; Shouju Wang; Feiyun Wu (Materials Today Bio)
Photodynamic therapy (PDT) efficacy in head and neck squamous cell carcinoma (HNSCC) is hindered by hypoxia and lactate accumulation in tumor microenvironment (TME), which suppress reactive oxygen species (ROS) generation and immune activation. To address this, we developed a carrier-free flexible dual-enzyme protein vesicle by covalently conjugating human serum albumin (HSA), catalase (CAT), and lactate oxidase (LOX) onto a mesoporous silica template, followed by template etching. Subsequently, the near-infrared photosensitizer IR808 was incorporated to obtain the final nanoparticle (HSA/CAT/LOX@IR808). This system employs a self-sustaining enzymatic cascade: CAT alleviates hypoxia by converting tumor-derived H2O2 into oxygen, while LOX depletes lactate and generates additional H2O2 to fuel CAT activity, synergistically amplifying ROS production. The flexible structure enhances tumor penetration of the nanoparticle, and the incorporation of HSA further enhances endothelial cell transport. In vitro and in vivo studies demonstrated the excellent biocompatibility, tumor-targeting capability, and TME remodeling effects of the vesicle. The vesicle triggered robust immune activation, characterized by M1 macrophage polarization, dendritic cell maturation, and CD8+ T cell infiltration. Ultimately, HSA/CAT/LOX@IR808-mediated PDT led to marked tumor inhibition, prolonged survival, and reduced metastasis. These findings underscore the potential of our protein vesicle as an effective and safe therapeutic approach for HNSCC.